SARS-CoV-2 and Asbestos Exposure: Can Our Experience With Mesothelioma Patients Help Us Understand the Psychological Consequences of COVID-19 and Develop Interventions? - Granieri, Antonella; Bonafede, Michela; Marinaccio, Alessandro; Iavarone, Ivano; Marsili, Daniela; Franzoi, Isabella Giulia (Frontiers in Psychology, 2020)
Since its emergence, the novel coronavirus disease of 2019 (Covid-19) has had enormous physical, social, and psychological impacts worldwide. The aim of this article was to identify elements of our knowledge on asbestos exposure and malignant mesothelioma (MM) that can provide insight into the psychological impact of the Covid-19 pandemic and be used to develop adequate interventions. Although the etiology of Covid-19 and MM differ, their psychological impacts have common characteristics: in both diseases, there is a feeling of being exposed through aerial contagion to an “invisible killer” without boundaries that can strike even the strongest individuals. In both cases, affected persons can experience personality dysfunction, anxiety, depression, and posttraumatic symptoms; helplessness, hopelessness, and projection of destructive thoughts onto external forces often emerge, while defense mechanisms such as denial, splitting, repression, and reduced emotional expression are used by individuals to contain their overwhelming anxieties. We believe that in both diseases, an integrated multidimensional intervention offered by hospitals and other public health services is the most effective approach to alleviating patients’ and caregivers’ psychological distress. In particular, we emphasize that in the context of both MM and Covid-19, Brief Psychoanalytic Group therapy can help patients and caregivers attribute meaning to the significant changes in their lives related to the experience of the disease, and identify adaptive strategies and more realistic relational modalities to deal with what has happened to them. We also highlight the importance of developing a surveillance system that includes individual anamnestic evaluation of occupational risk factors for Covid-19 disease.